Rediscovering heritage through artefacts, sites, and landscapes : translating a 3500-year record at Ritidian, Guam - Carson, Mike T., (Archaeopress Publishing Ltd, 2017)
The Ritidian Site in Guam reveals the full scope of traditional cultural heritage in the Mariana Islands since 1500 B.C. The material records here have been incorporated into a cohesive narrative in chronological order to learn about the profound heritage of this special site and its larger research contributions.